2023
DOI: 10.1001/jamanetworkopen.2023.18620
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Meningioma and Breast Cancer

Abstract: ImportanceA potential relationship between meningioma and breast cancer was suggested 70 years ago. However, to date, no conclusive evidence is available on this topic.ObjectiveTo provide a comprehensive review of the literature on the association of meningioma with breast cancer, supported by a meta-analysis.Data SourcesA systematic PubMed search was performed up to April 2023 to identify articles on the association of meningioma with breast cancer. The following key words were used strategically: meningioma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…However, previous pregnancy does not appear to be an unequivocal risk factor for meningioma 9. Studies have also shown a link, albeit a weak one, between breast cancer and meningiomas 10…”
Section: Introductionmentioning
confidence: 94%
“…However, previous pregnancy does not appear to be an unequivocal risk factor for meningioma 9. Studies have also shown a link, albeit a weak one, between breast cancer and meningiomas 10…”
Section: Introductionmentioning
confidence: 94%
“…It has been suggested that the difference in incidence is related to the different levels of hormones between males and females, because meningiomas are known to have progesterone and oestrogen receptors that can influence the response of the tumour to sex hormones [47,51,52]. Other studies have focused on the connection between breast cancer and meningioma in relation to hormone levels because breast cancer has wellestablished hormonal involvement and patients with meningiomas are more likely to develop breast cancer [53]. Other studies conducted in females who received cyproterone acetate (a synthetic progestin) to treat severe cases of hirsutism suggested that this hormonal therapy increases the incidence of meningioma [54].…”
Section: Meningiomamentioning
confidence: 99%
“…Meningiomas originate from arachnoid cap cells, are usually estimated to grow 2–4 mm/year and are slightly more common in females [ 2 4 ]. Several risk factors for meningioma development have been investigated, with age, radiation and sex hormones being most commonly reported as elevating the risk of the disease [ 5 , 6 ], while smoking, hypertension and the metabolic syndrome still being mostly inconclusive as risk factors [ 2 4 ]. According to the current WHO classification [ 7 ], roughly 80% of meningiomas are considered grade 1 lesions, with a 10-year overall survival rate of up to 90%.…”
Section: Introductionmentioning
confidence: 99%